Penerapan Logika Fuzzy Sugeno untuk Menentukan Reward pada Game Edukasi Platformer Berbasis Android - Sanjaya, Ahdi; Wahyudi , Jusuf; Arliando , Yode (MEANS (Media Informasi Analisa dan Sistem), 2022)
The development of information and communication technology devices makes the teaching and learning process easier and more fun, students are now not only able to learn from books but can also learn from various other media such as games. The use of games in the teaching and learning process will make it easier for students to understand concepts in learning. By applying games in the teaching and learning process, it can increase students' motivation and interest in learning. The purpose of this research is to build a game that is fun and can help students in learning.In this game, Sugeno fuzzy logic is applied which serves to determine the rewards / bonuses that players will get when completing the challenges of each level.